2007
DOI: 10.1287/mnsc.1060.0625
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in Evolving Social Networks

Abstract: We study the problem of cooperative behavior emerging in an environment where individual behaviors and interaction structures coevolve. Players not only learn which strategy to adopt by imitating the strategy of the best-performing player they observe, but also choose with whom they should interact by selectively creating and/or severing ties with other players based on a myopic cost-benefit comparison. We find that scalable cooperation--that is, high levels of cooperation in large populations--can be achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(168 citation statements)
references
References 34 publications
3
163
2
Order By: Relevance
“…Marsili et al (2005) highlight the importance of the clustering degree for sustaining cooperation. Zimmermann et al (2004), Fosco and Mengel (2008) or Hanaki et al (2007) among many others explain cooperation through exclusion of non-cooperators in a dynamic network setting. The role of a conformist bias in imitation has been examined by Ellison and Fudenberg (1993) to study the spread of an efficient technology in a one person decision problem.…”
Section: Introductionmentioning
confidence: 99%
“…Marsili et al (2005) highlight the importance of the clustering degree for sustaining cooperation. Zimmermann et al (2004), Fosco and Mengel (2008) or Hanaki et al (2007) among many others explain cooperation through exclusion of non-cooperators in a dynamic network setting. The role of a conformist bias in imitation has been examined by Ellison and Fudenberg (1993) to study the spread of an efficient technology in a one person decision problem.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a careful examination of these feedbacks has lead to results that are at odds with previously shared wisdom on what type of social structure promotes cooperation. In particular, Hanaki et al (2007) have shown how the survival of a cooperating population requires sparse networks, little local clustering, and the possibility that agents unilaterally cut unprofitable ties. This findings are at odds with the prior wisdom that cooperation would develope in closed and dense communities of cooperators (see Axelrof, 1984, Coleman, 1988.…”
Section: Evolution Of Cooperation In Networkmentioning
confidence: 99%
“…If, however, the population starts being relatively indifferent with respect to tags (b = 2.00), and there are no search costs, then the population may or may not evolve into one that cares about tags (see and lines in Figure 12). Hanaki et al (2004): trust Hanaki et al (2004) study a repeatedly played one-shot version of a standard Prisoner's Dilemma (PD) game. Just as Ashlock et al (1996), they start from the observation that defection is the dominant strategy, and ask the question whether cooperation could be sustained with endogenously determined local interactions, with the individual agents choosing their (number of) partners.…”
Section: Riolo (1997): Arbitrary Tagsmentioning
confidence: 99%
“…That is, although the agents update their trust levels, they do not learn on which interactions they should base their trust. Hanaki et al (2004) present an extensive analysis for a wide range of parameter values. Figure 14 shows the relative frequency distribution of average cooperation levels reached in 10 000 runs of 10 000 periods for a population of 1000 agents, with the other parameter values sampled randomly from pre-specified ranges.…”
Section: Riolo (1997): Arbitrary Tagsmentioning
confidence: 99%